Is the Polish Labour Market Heading Towards Polarisation? - Arendt, Łukasz (Olsztyn Economic Journal, 2018)
The paper discusses the nature of technical change in the Polish labour market, referring to two dominant hypotheses: Skill-Biased Technical Change and Routinisation-Biased Technical Change. The goal of the study is to test the hypothesis of the polarisation of the Polish labour market. The empirical analysis revealed that the Polish labour market does not follow the typical polarisation path identified in developed countries. It appeared that the biggest decline in labour demand has not been observed in the middle of skills/wage distribution. Technical change has led to skills upgrading, however, employment and wages in the group of low-skilled workers have not deteriorated much. Moreover, major changes in the task content of jobs have occurred in Poland. These changes are consistent with patterns of the developed countries with the exception of routine cognitive tasks, for which demand has increased in the last decade. The results of the analysis are ambiguous – shifts in the structure of employment and wages in Poland seem to be stuck between scenarios offered by SBTC and RBTC hypotheses.